Machine Learning and Deep Learning Approaches in Breast Cancer Survival Prediction Using Clinical Data - Kalafi, E Y; Nor, N A M; Taib, N A; Ganggayah, M D; Town, C; Dhillon, S K (Folia biologica, 2019)
Breast cancer survival prediction can have an extreme effect on selection of best treatment protocols. Many approaches such as statistical or machine learning models have been employed to predict the survival prospects of patients, but newer algorithms such as deep learning can be tested with the aim of improving the models and prediction accuracy. In this study, we used machine learning and deep learning approaches to predict breast cancer survival in 4,902 patient records from the University of Malaya Medical Centre Breast Cancer Registry. The results indicated that the multilayer perceptron (MLP), random forest (RF) and decision tree (DT) classifiers could predict survivorship, respectively, with 88.2 %, 83.3 % and 82.5 % accuracy in the tested samples. Support vector machine (SVM) came out to be lower with 80.5 %. In this study, tumour size turned out to be the most important feature for breast cancer survivability prediction. Both deep learning and machine learning methods produce desirable prediction accuracy, but other factors such as parameter configurations and data transformations affect the accuracy of the predictive model.
Keywords: demografie; Young Adult; analýza přežití; deep learning; Middle Aged; Decision Trees; mladý dospělý; Demography; neuronové sítě; Adult; Aged; dospělí; Neural Networks, Computer; nádory prsu; senioři; rozhodovací stromy; kalibrace; Deep Learning; Survival Analysis; senioři nad 80 let; lidé; ženské pohlaví; Breast Neoplasms; Humans; Support Vector Machine; Aged, 80 and over; Female; Calibration; lidé středního věku; support vector machine